Price determination in public offering and evaluation methods - Hacıoğlu, Ümit; Dinçer, Hasan; Akça, Zuhal (IGI Global, 2017)
The latest financial situation in capital markets in advanced economies, emerging markets, and the Euro zone illustrates that volatility and risks related to global economic activity and global financial markets have impact on local capital markets and directly affects the value of company stocks even though an investor diversified his/her risk by investing in a portfolio. The initial public offering process, performance evaluation methods, and price determination became key factors for companies and investors. In this chapter, advantages and disadvantages of IPO, pricing methods and performance evaluation methods are assessed.
Keywords: Price Determination; Public Offering; Evaluation Methods